Formulation and characterization of Piper belle nanoemulgel for anti-microbial activities - Amat Rahim, Nor Fadiana (2020)
The aim of this study was to formulate and characterize the nanoemulgel containing Piper betle essential oil. The nanoemulgel was formulated using blank nanoemulsion (FO), nanoemulsion with 1:4 (F1) and 4:1 (F2) ratio of soybean oil to Piper betle oil and thickening agent. The formulation of nanoemulgel was done based on the ternary phase diagram from the previous study that produced a large nanoemulsion region. The essential oil of Piper betle was extracted by using steam distillation method and analysed by using Fourier Transform Infrared (FTIR) to observe the functional group present. The mean droplet size of nanoemulsion were 41.00 nm, 161.05nm, and 27.67 nm for FO, Fl, and F2 respectively. It was confirmed by Dynamic Light Scattering (DLS). Nanoemulsion and nanoemulgel were characterised by using Tyndall effect, physical appearance test, spreadability test and pH test. The Piper betle nanoemulgel produced was tested on Staphylococcus aureus to investigate its affectiveness on antimicrobial activity. The antimicrobial assay test was conducted to measure the diameter of inhibition zone of Staphylococcus aureus. The statistical analysis shows that there was a significant differences between the groups (p < 0.05). Nanoemulgel can be used to serve a better stability, permeation and suitable viscosity for the delivery of drugs. Nanoemulgel can influences a better skin penetration as it consist of small droplets size containing essential oil as the active ingredient.